ANALYSIS OF DOMES IN TOMB ARCHITECTURE OF DELHI: EVOLUTION AND GEOMETRICAL TRANSITION - Sahil Ali Khan; Mohammad Arif Kamal (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
The dome is a vital element and a prominent building feature in Islamic Architecture. This paper analyzes the geometrical and philosophical approach to the transition of two types of domes, i.e., square and octagonal base domes. The timeline and region selected for the work are from the 1420s to 1630s of the Indian subcontinent. During the period, it covers three dynasties: Sayyid Dynasty, Lodi Dynasty, and Mughal Dynasty, and their change of approach toward the shapes of domes according to the needs and availability of construction techniques at hand and other factors. Based on the comparison of the domes of four buildings, the evolution of domes and their need for transition is to be presented in this work.